Application of hybrid anaerobic reactor: Treatment of increasing cyanide containing effluents and microbial composition identification. (15th November 2018) - Gupta, Pragya; Sreekrishnan, T.R.; Shaikh, Z.A.
Abstract: The study endeavors the anaerobic treatment of cyanide-containing effluents using the hybrid anaerobic reactor, with self-immobilized granules under high up-flow velocities. Comparison of one-year time-course analyses of HARs treating high strength effluents containing cyanide and control indicates the importance of wastewater characteristics in development and maintenance of microbiome. Efforts were directed towards associating process performance with microbial dynamics. Presence of cyanide results in the accumulation of intermediates paralleled with a drop in abundance of sensitive aceticlastic methanogens. HAR appear to have better resilience than other identified digesters because of shielding effects and enhanced granule-wastewater contact. The predominance of Methanobacteriales in the presence of cyanide can be linked to its tolerance. It was found that methane yield is positively correlated with abundance of aceticlastic guilds (R = 0.830, CI = 0.01). Tolerant bacterial groups were also identified. The study advances our knowledge related to less energy intensive technology with the focus on the development of efficient HAR. Graphical abstract: Image 1 Highlights: Hybrid anaerobic reactor (HAR) had higher resilience than other high rate systems. Temporal analysis of HAR demonstrated achievement of higher inhibition threshold. Anaerobic microbiome structure was strongly linked with the process parameters. Clostridiales and Methanobacteriales appeared as most tolerant microbial groups. Higher up-flow velocities resulted in achievement of higher efficiencies.